2008
DOI: 10.1007/s10725-008-9314-3
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid inhibits in vitro rooting in mung bean [Vigna radiata (L.) Wilczek] hypocotyls by inducing oxidative stress

Abstract: Caffeic acid (CA), which is ubiquitously present in plants, is a potent phytotoxin affecting plant growth and physiology. The aim of our study was to investigate whether CA-induced inhibition of adventitious root formation (ARF) in mung bean {Vigna radiata (L.) Wilczek [Phaseolus aureus Roxb.]} involves the induction of conventional stress responses. The effect of CA (0-1000 lM) on ARF in mung bean was determined by measuring the generation of reactive oxygen species (ROS) in terms of malondialdehyde and hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 39 publications
(36 reference statements)
3
21
0
Order By: Relevance
“…Moreover, PODs activity increases significantly in response to allelochemicals, including phenolic acids (Baziramakenga et al 1995;Weir et al 2004). Singh et al (2009) demonstrated that caffeic acid inhibits root growth through generation of reactive oxygen species (ROS) in Phaseolus aureus. Baziramakenga et al (1995) demonstrated that phenolic acids undergo oxidation to form quinines that are highly reactive free radicals.…”
Section: Fa Induces Biochemical Changes In Mung Bean Hypocotylsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, PODs activity increases significantly in response to allelochemicals, including phenolic acids (Baziramakenga et al 1995;Weir et al 2004). Singh et al (2009) demonstrated that caffeic acid inhibits root growth through generation of reactive oxygen species (ROS) in Phaseolus aureus. Baziramakenga et al (1995) demonstrated that phenolic acids undergo oxidation to form quinines that are highly reactive free radicals.…”
Section: Fa Induces Biochemical Changes In Mung Bean Hypocotylsmentioning
confidence: 99%
“…Nevertheless, phenolic acids interfere with the activity of plant growth regulators like auxins and cytokinins (Einhellig 2004). Further, we did not explore whether the observed reduction in the rooting of mung bean hypocotyls involve any induction of oxidative stress through ROS generation, since phenolics have been reported to affect plant growth through oxidative stress induction (Weir et al 2004;Oracz et al 2007;Singh et al 2009). …”
Section: Fa Induces Biochemical Changes In Mung Bean Hypocotylsmentioning
confidence: 99%
“…For example, heat pretreatment mitigates chilling stress of plants through regulating antioxidant activities (Zhang et al, 2005); pre-acclimation to drought stress (Khanna-Chopra and Selote, 2007) and cold conditions (Tao et al, 1998) influences antioxidant activities in relation to stress resistance in plants. Salicylic acid, caffeic acid and other natural or synthetic molecules can create oxidative stress in plant cells and tissues (Ganesan and Thomas, 2001;Singh et al, 2009). However, when applied exogenously at suitable concentrations, salicylic acid enhances the efficiency of the antioxidant system and alleviates chilling stress of seedlings (Hayat et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the exposure to caffeic acid, an increase of the lipid peroxidation process was observed in the root of bean [23] and cabbage [24]. In this research, C. menthifolium aqueous extract which contains caffeic acid at a concentration of 13.9 ± 0.7µg/g, induced lipid peroxidation in black nightshade leaves and roots.…”
Section: Antioxidant Enzyme Activity and Mda Contentmentioning
confidence: 51%